Glycemic index and endurance performance - Donaldson, C. M.; Perry, T. L.; Rose, M. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
The aim of this review is to provide an up-to-date summary of the evidence surrounding glycemic index (GI) and endurance performance. Athletes are commonly instructed to consume low-GI (LGI) carbohydrate (CHO) before exercise, but this recommendation appears to be based on the results of only a few studies, whereas others have found that the GI of CHO ingested before exercise has no impact on performance. Only 1 study was designed to directly investigate the impact of the GI of CHO ingested during exercise on endurance performance. Although the results indicate that GI is not as important as consuming CHO itself, more research in this area is clearly needed. Initial research investigating the impact of GI on postexercise recovery indicated consuming high-GI (HGI) CHO increased muscle glycogen resynthesis. However, recent studies indicate an interaction between LGI CHO and fat oxidation, which may play a role in enhancing performance in subsequent exercise. Despite the fact that the relationship between GI and sporting performance has been a topic of research for more than 15 yr, there is no consensus on whether consuming CHO of differing GI improves endurance performance. Until further well-designed research is carried out, athletes are encouraged to follow standard recommendations for CHO consumption and let practical issues and individual experience dictate the use of HGI or LGI meals and supplements before, during, and after exercise.